ANALISIS SISTEM PENYELENGGARAAN PELAYANAN OBSTETRI NEONATAL EMERGENSI DASAR (PONED) DALAM MENINGKATKAN MUTU PELAYANAN DI PUSKESMAS MAMPU PONED KOTA PAYAKUMBUH - Delviana, Delviana; Astiena, Adila Kasni (Ensiklopedia of Journal, 2024)
Basic Emergency (PONED) in Improving the Quality of Services at the Capable Poned Health Centre in Payakumbuh City. The research was conducted at the Capable PONED Community Health Centre, Payakumbuh City. There were 12 informants in this research, consisting of the Head of the PONED Community Health Centre (Ibuh and Lampasi), the PONED Doctor (Ibuh and Lampasi), the PONED Midwife (Ibuh and Lampasi), the PONED Nurse (Ibuh and Lampasi), the Regional Guidance Midwife (Ibuh Dan Lampasi), and PONED Patients at the PONED Health Centre (Ibuh and Lampasi). This research uses interview and observation data analysis techniques where there are three lines of data analysis, namely data reduction, data presentation, and drawing conclusions. The research results show that overall, the Payakumbuh City PONED Capable Community Health Centre has faced various challenges and taken steps to improve the quality of PONED services. Continuous efforts are needed to ensure that all service standards and needs are met optimally for the welfare of obstetric and neonatal patients. Keywords: Implementation System, PONED, Service Quality, Payakumbuh Community